PENERAPAN METODE GROSS UP ATAS PERHITUNGAN PPH PASAL 21 SEBAGAI ALTERNATIF EFISIENSI PAJAK - Setiawan, Hendra Adi; Mildawati, Titik (Jurnal Ilmu dan Riset Akuntansi (JIRA), 2017)
ABSTRACTThis research is meant to find out how the impact of the implementation of gross-up method to the calculation of income tax article 21 and whether it can be used as an alternative to tax efficiency. The method has been carried out by using descriptive qualitative and the primary data, documentation and interview. The result of the research shows that by using gross-up method to the implementation of the salary data in 2015 has made the allowance of income tax Article 21 which has been provided by the company is equal to the payable income tax Article 21, implementation of the gross-up method has made salary cost increases so that the employee income tax Article 21 also increases as well, expense account income tax Article 21 which is affected by the fiscal correction in L / R corporate fiscal will be removed and will be replaced by the allowance of income tax Article 21 is not affected by the fiscal correction so it will reduce the fiscal profit before corporate tax. It can be concluded from the result of the research that by using the gross-up metyhod the company is able to reduce the burden of corporate income tax.Keywords: Gross up method, tax efficiency, income tax Article 21.